THE CORRELATION BETWEEN LEARNING MEDIA USAGE AND READING HABIT TOWARD READING ACHIEVEMENT AT THE FIRST YEAR OF MAN KRECEK-KEDIRI - Rizqia, Iva (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 8 No 3 (2018): LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
This research is to explain the correlation between learning media usage and reading habit toward reading achievment at first year of MAN Krecek. This research uses the descriptive quantitative approach; the method used correlation and the technique to get data by using questionnare and test. The population is the student at the first year at MAN Krecek and the sample is 101 students. Next, the data computed and analyze by using SPSS version 16.0 and Microsoft Excel program. There are two results, the first result is simultaneous correlation between learning media usage and reading habit toward reading achievement, the value of correlation computation by using SPSS is 0.28,1. It can be seen that the significance level is 2-tailed. It means level significance is in the 0.01 or 1%. Finally, based on the result of this research, it can conclude that there is significant correlation between learning media and reading habit toward reading achievement among the first year students of MAN Krecek. The second result is partial correlation between learning media and reading achievement controlled by reading habit. The value is -0,015. It can be seen that the significance level is 2-tailed. It means the level significance is in the 0.01 or 1%. The result shows that there is not positive significant correlation between learning media and reading achievement controlled reading habit.